Prediction of Thiopurine Metabolite Levels Based on Haematological and Biochemical Parameters - Hradsky, Ondrej; Potuznikova, Kristyna; Siroka, Jitka; Lerchova, Tereza; Urbanek, Lubor; Mihal, Vladimir; Spenerova, Michaela; Velganova-Veghova, Maria; Karaskova, Eva; Bronsky, Jiri (Journal of pediatric gastroenterology and nutrition, 2019)
OBJECTIVES: Therapeutic drug monitoring of thiopurine erythrocyte levels is not available in all centers and it usually requires quite a long time to obtain the results. The aims of this study were to build a model predicting low levels of 6-thioguanine and 6-methylmercaptopurine in pediatric inflammatory bowel disease (IBD) patients and to build a model to predict nonadherence in patients treated with azathioprine (AZA). METHODS: The study consisted of 332 observations in 88 pediatric IBD patients. Low AZA dosing was defined as 6-thioguanine levels <125 pmol/8 × 10 erythrocytes and 6-methylmercaptopurine levels <5700 pmol/8 × 10 erythrocytes. Nonadherence was defined as undetectable levels of 6-thioguanine and 6-methylmercaptopurine <240 pmol/8 × 10 erythrocytes. Data were divided into training and testing part. To construct the model predicting low 6-thioguanine levels, nonadherence, and the level of 6-thioguanine, the modification of random forest method with cross-validation and resampling was used. RESULTS: The final models predicting low 6-thioguanine levels and nonadherence had area under the curve, 0.87 and 0.94; sensitivity, 0.81 and 0.82; specificity, 0.80 and 86; and distance, 0.31 and 0.21, respectively, when applied on the testing part of the dataset. When the final model for prediction of 6-thioguanine values was applied on testing dataset, a root-mean-square error of 110 was obtained. CONCLUSIONS: Using easily obtained laboratory parameters, we constructed a model with sufficient accuracy to predict patients with low 6-thioguanine levels and a model for prediction of AZA treatment nonadherence (web applications: https://hradskyo.shinyapps.io/6TG_prediction/ and https://hradskyo.shinyapps.io/Non_adherence/).
Keywords: biologické modely; Female; dítě; ženské pohlaví; monitorování léčiv; erytrocyty; Adolescent; Predictive Value of Tests; prediktivní hodnota testů; Inflammatory Bowel Diseases; lidé; Models, Biological; Immunosuppressive Agents; Sensitivity and Specificity; senzitivita a specificita; Thioguanine; Mercaptopurine; Medication Adherence; Humans; adherence k farmakoterapii; Male; Erythrocytes; thioguanin; Drug Monitoring; idiopatické střevní záněty; Child; plocha pod křivkou; mužské pohlaví; merkaptopurin; imunosupresiva; mladiství; Area Under Curve